ANALISIS TEMUAN BASIL TAHAN ASAM PADA SPUTUM CARA LANGSUNG DAN SEDIAAN KONSENTRASI PADA SUSPEK TUBERKULOSIS - Elisabeth Frida; S. Ibrahim; Hardjoeno Hardjoeno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2005)
Tuberculosis is still an important health problem in Indonesia, being the third place in the world. The diagnosis could be done bydirect microscopic method of slides stained with Ziehl Neelsen. The finding of AFB could be improved by decontaminating the specimensto provide a concentrated sample. To analyze the findings of AFB through microscopy and concentrated smear methods, comparing ofeach to bacteriological culture. Diagnosis was done on 148 patients during May to September 2005, using microscopic method (directmicroscopy and concentrated smear) and culture. Analysis of results was done by using SPSS for Window v. 11.5. Of the 148 specimens,15 (10.1%) and 55 (37.2%) positive AFB were found in direct microscopy and concentrated smears respectively. The sensitivities indirect microscopy and concentrated smears were 22% and 64.8%, while the specificities were 96.8% and 78.7%, positive predictivevalues (PPV) were 80% and 63.6%, negative predictive values (NPV) 68.4% and 79.5%, accuracy values were 69.5% and 73.6%. Thespecificity and PPV were higher in direct microscopic method, while positive value, sensitivity, NPV and accuracy value were higher indecontamination, concentrated sample method. Concentrated sample method will increase the accuracy of the finding of Ziehl NeelsenstainedAFB so that this method could be assumed better for use.